DESEMINASI: PEMBUATAN AIR BERSIH DENGAN MEMANFAATKAN AIR HUJAN MELALUI PENYARING PIPA BERSUSUN BERBASIS ADSORBEN ALAMI - Erma Handarsari; Fitria Fatichatul Hidayah; Yunan Kholifatuddin Sya’di (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The availability of clean water is a basic need for the community. Meteseh Urban Village is one of the areas that get medium water drainage from PDAM Semarang, so that the drainage of water is rotated, that is the drainage of a day with the flowing time at certain hours. Consequences that must be done by citizens who mostly subscribe to PDAM is to prepare the upper and lower tandon so that when the water does not flow there is still water stock. During the rainy season, when the rainfall is high enough people do not use it to be accommodated in the lower tank because it still contains dirt, germs and pH can be below 7. The purpose of this study is the use of the lower reservoir for the provision of clean water from rain water by applying the water filter pipe method arranged. The methods used are preparation of tools and materials, Socialization, Counseling and Training, Practice of pipe filtering, Counseling and Evaluation activities and installation of a pipe-level water filter method at the lower tanks owned by representatives of neighborhood RT 02 and RT 03, RW 11 sub-districts Meteseh. Pipe filter is compiled using materials that are easy to get by citizens and environmentally friendly are ijuk, gravel, sand, coconut shell charcoal, and spoon. The results of this research are: the community has used rain water as clean water, reducing the burden of PDAM water usage,the utilization of natural adsorbent so that people are able to implement independently and sustainably. The community is able to install and operate the filters easily. The use of sand adsorbents can provide higher clarity.Keywords: Water filter, pipeline, Water Tandon, PDAM, Natural Adsorbent